Royalty Taxation under Tax Competition and Profit Shifting - Steffen Juranek; Dirk Schindler; Andrea Schneider (Center for Economic Studies and ifo Institute (CESifo), 2018)
The increasing use of intellectual property as a means to shift profits to low-tax jurisdictions or jurisdictions with so-called `patent boxes' is a major challenge for the corporate tax base of medium- and high-tax countries. Extending a standard tax competition model for capital-enhancing technology, royalty payments, and profit shifting, this paper suggests a simple fix: It is optimal to set a withholding tax on (intra-firm) royalty payments equal to the corporate tax rate and deny any deductibility of royalties. As the tax applies to the full payment, the problem of identifying the arm's-length component in a digital economy (OECD BEPS Action 1) does not apply. Most importantly, the denial of royalty deductions is the Pareto-efficient solution under coordination and the unilaterally optimal policy under competition for mobile capital. In the latter case, a weakened thin capitalization rule is a crucial part of the policy package in order to avoid negative investment effects. Our results question the ban of royalty taxes in double tax treaties and the EU Interest and Royalty Directive.
Keywords: H25; F23; 330; source tax on royalties; tax competition; multinationals; profit shifting